Comparative effectiveness of tumour necrosis factor α inhibitors in combination with either methotrexate or leflunomide. Issue 12 (6th January 2009) - Strangfeld, A; Hierse, F; Kekow, J; von Hinueber, U; Tony, H-P; Dockhorn, R; Listing, J; Zink, A
Abstract : Objective: The objective of this study was to compare the effectiveness of a combination of tumour necrosis factor α (TNFα) inhibitors with either methotrexate or leflunomide in the treatment of patients with rheumatoid arthritis in a real-world setting. Methods: Data from 1769 outpatients enrolled in the German biologics register RABBIT who were treated with one of the TNFα inhibitors adalimumab, etanercept, or infliximab in combination with either methotrexate (n  =  1375) or leflunomide (n  =  394) were included in the analysis. Clinical status including disease activity as well as treatment data were documented by the treating rheumatologist at baseline and at 3, 6, 12, 18, 24, 30 and 36 months of follow-up. Results: Patients treated with a combination of biologics with leflunomide had significantly higher baseline disease activity than those treated with methotrexate. The highest disease activity was found for patients treated with the combination infliximab/leflunomide. After 36 months, the discontinuation rates were 46.3%, 51.3% and 61.5% for combinations of etanercept, adalimumab and infliximab with methotrexate and 53.4%, 63.1% and 67.1% for combinations with leflunomide, respectively. European League Against Rheumatism response rates after 24 months ranged from 74% to 81% for combinations with methotrexate and 72% to 81% for combinations with leflunomide. Conclusion: The current clinical practice is to use methotrexate as a first choice for the combination with TNFα antagonists. In a number of patients methotrexate has to be replaced by another disease-modifying antirheumatic drug. Our data support the view that leflunomide is a useful alternative if methotrexate is contraindicated.